Plastome Phylogenomics of Aucuba (Garryaceae) - Huang, Yuan; Fan, Linyuan; Huang, Jian; Zhou, Guohua; Chen, Xiong; Chen, Jiahui (Frontiers in Genetics, 2022)
Aucuba (Garryaceae), which includes approximately ten evergreen woody species, is a genus endemic to East Asia. Their striking morphological features give Aucuba species remarkable ornamental value. Owing to high levels of morphological divergence and plasticity, species definitions of Aucuba remain perplexing and problematic. Here, we sequenced and characterized the complete plastid genomes (plastomes) of three Aucuba species: Aucuba chlorascens, Aucuba eriobotryifolia, and Aucuba japonica. Incorporating Aucuba plastomes available in GenBank, a total of seven Aucuba plastomes, representing six out of ten species of Aucuba, were used for comparative plastome analysis, phylogenetic analysis and divergence time estimation in this study. Comparative analyses revealed that plastomes of Aucuba are highly conserved in size, structure, gene content, and organization, and exhibit high levels of sequence similarity. Phylogenetic reconstruction based on 68 plastid protein-coding genes strongly supported the monophyly of Garryales, Garryaceae and Aucuba. Aucuba eriobotryifolia was sister to the other Aucuba species examined, consistent with its unique fused anther locule. The divergence time of Aucuba was estimated to be approximately late Miocene. Extant Aucuba species derived from recent divergence events associated with the establishment of monsoonal climates in East Asia and climatic fluctuations.